Isolation and characterization of bacteria from rusted iron materials - Khan, Muhbubar Rahman; Saha, Mihir Lal; Begum, Nahmina; Islam, Mohammad Nurul; Hoque, Sirajul (Bangladesh Journal of Botany, 2011)
Seventy bacterial isolates were recovered from different rusted iron materials using modified NP glucose, 9K and sulfur oxidizing media. Thirty four isolates were selected after primary screening on the basis of their growth in modified NP glucose medium. Out of 34 isolates 5 belonged to the genus Kurthia, 6 Thiobacillus, 16 Bacillus and remaining 7 were Acidiphilium, Oscillospira, Sulfobacillus, Alicyclobacillus, Neisseria, Pseudomonas and Rahnella. One of the isolated organisms, Bacillus megaterium (F16/2), was found to be thermophilic. The organisms showed better growth in presence of iron salts like ferrous sulfate, ferric sulfate and ammonium ferric citrate. Five isolates were found to transform ferrous (Fe2+) to ferric (Fe3+) of which Bacillus subtilis (F8) was most efficient. A good number of bacteria were associated with oxidation of iron. Key words: Isolation; Bacteria; Rusted iron; Transformation DOI: 10.3329/bjb.v39i2.7479 Bangladesh J. Bot. 39(2): 185-191, 2010 (December)